1,000 undergraduates liven up green campus programme - UMP, PNC
More than 1,000 Universiti Malaysia Pahang (UMP) undergraduates in Pekan campus turned up to take part in the Green Campus programme and No Plastic Bag On Saturday campaign aimed at enhancing awareness on preserving nature.